The Role of Emotional Intelligence in Financial Competence - Rahman, Ahmad Vajri; Khairi, Awalul; Dika, Riri Putri (Universitas Tanjungpura, 2024)
This research investigates the intricate relationship between emotional intelligence, financial education, financial behavior, and financial competence among employees at PT. PPI Cabang Padang. Using path analysis, the study examines both direct and indirect effects of emotional intelligence and financial education on financial competence through financial behavior. The findings reveal significant direct effects of emotional intelligence and financial education on financial competence, highlighting their crucial roles in shaping individuals' financial capabilities. Additionally, the analysis uncovers significant indirect effects of emotional intelligence and financial education on financial competence through their influence on financial behavior. Metodologi penelitian menggunakan desain kuantitatif dengan menggunakan random sampling untuk memilih sampel sebanyak 70 karyawan PT. PPI Cabang Padang. These results underscore the importance of fostering emotional intelligence skills and providing comprehensive financial education within the organization to promote positive financial behaviors and enhance overall financial competence among employees. By integrating targeted interventions and education initiatives, PT. PPI Cabang Padang can empower its workforce to make informed financial decisions, ultimately leading to greater financial stability and success for both individuals and the organization.